Ethical and Deontological Violations as a Side Effect in Value-Based Healthcare: Monitoring Instruments - E. V. Smirnova (Здоровье мегаполиса, 2024)
It is important to adhere to ethical standards of medical care at any stage or level of societal development. Since healthcare systems have widely integrated digital technologies and the principle of value-based healthcare has been firmly embedded in the practice of healthcare organizations, the ethical challenges have become highly relevant.Paradoxically, the defects related to violations of medical ethics and deontology by healthcare professionals are not listed in the current order of the Ministry of Health of the Russian Federation regulating the quality control of medical care for compulsory medical insurance. As a result, there are no mechanisms for applying financial sanctions to healthcare organizations. Also, some issues, such as violation recoding and a possible subjective patient’s assessment of doctors’ actions, are still to be addressed.The author considered the doctor-patient relationship and the mechanism for recording violations of ethics and deontology defined by the order of Moscow Healthcare Department.